Project of a critical collection of viceregal reports - Hanke, Lewis (Revista Chilena de Historia del Derecho, 1970)
Spain established in America one of the most extensive empires the World has ever seen, and developed a remarkable bureaucratic structure to govern it. The key official was the Viceroy, the personal representative of the King in the two great viceroyalties organized in Mexico and Peru shortly after they were conquered in the early years of the sixteenth century.